Redução de danos e teologia: protagonizando novas compreensões de vida e cuidado a partir da epidemia de HIV/AIDS - Konig, Claudio Roberto (2013)
The present study‟s research object is to discuss, from the experience acquired with the Harm Reduction Program, new understandings of life and care from the HIV/AIDS epidemic. Starting with this, it proposes in the interface with Theology, pastoral action alternatives that rescue and promote respect for human dignity not only for people living with HIV/AIDS and/or living together with people living with HIV/AIDS, but all who for one reason or another are vulnerable and/or have their rights violated, no matter which sphere of society they are part of. The goals of this research are to present the proposals of the Harm Reduction Program, as well as see the way it constructed the concept of human dignity from this proposals together with Theology and pastoral work by ministers of the Igreja Evangélica de Confissão Luterana no Brasil (IECLB) who worked in the Harm Reduction Program. After presenting the experiences of those ministers, an experience of table communion in the model of Jesus Christ, with a person with Aids attended by the Harm Reduction Program is presented and reflected upon. At last, contributions are constructed and proposed as a result of the Harm Reduction Program in dialogue with Theology, contributing to the construction of new understandings of life and care from the HIV/AIDS epidemic. Concerning methodology, the research took place in two moments. The first one is bibliographic, dealing with works that discuss the issues of drugs in relation to the Aids epidemic and describe the context in which the Harm Reduction emerges, works that discuss contemporary table communions, works that discuss a possible Theology of Aids. In a second moment, a field research was accomplished, presenting interviews with four pastors from the IECLB to understand the meanings the harm reduction proposals offered them, for their private lives as well as for the pastoral work accomplished in their congregations. In conclusion, from the empirical knowledge of harm reduction in face of the theme of HIV/AIDS, new proposals for life and care are presented so that contemporary churches may, from the reality of their congregations, promote life and human dignity.